Inhibition of TGF-β signaling, invasion, and growth of cutaneous squamous cell carcinoma by PLX8394 - Siljamäki Elina; Riihilä Pilvi; Suwal Ujjwal; Nissinen Liisa; Rappu Pekka; Kallajoki Markku; Kähäri Veli-Matti; Heino Jyrki (Nature Publishing Group, 2025)
Cutaneous squamous cell carcinoma (cSCC) is the most common metastatic skin cancer. The prognosis of patients with metastatic cSCC is poor emphasizing the need for new therapies. We have previously reported that the activation of Ras/MEK/ERK1/2 and transforming growth factor β (TGF-β)/Smad2 signaling in transformed keratinocytes and cSCC cells leads to increased accumulation of laminin-332 and accelerated invasion. Here, we show that the next-generation B-Raf inhibitor PLX8394 blocks TGF-β signaling in ras-transformed metastatic epidermal keratinocytes (RT3 cells) harboring wild-type B-Raf and hyperactive Ras. PLX8394 decreased phosphorylation of TGF-β receptor II and Smad2, as well as p38 activity, MMP-1 and MMP-13 synthesis, and laminin-332 accumulation. PLX8394 significantly inhibited the growth of human cSCC tumors and in vivo collagen degradation in xenograft model. In conclusion, our data indicate that PLX8394 inhibits several serine-threonine kinases in malignantly transformed human keratinocytes and cSCC cells and inhibits cSCC invasion and tumor growth in vitro and in vivo. We identify PLX8394 as a potential therapeutic compound for advanced human cSCC.